Investigation of nanosecond pulse dielectric barrier discharges in still air and in transonic flow by optical methods. (9th December 2015) - Peschke, P; Goekce, S; Leyland, P; Ott, P
Abstract: In the present study the interaction of nanosecond pulsed dielectric barrier discharge (ns-DBD) actuators with aerodynamic flow up to transonic velocities was investigated. The primary focus was on the influence of the flow on the discharge and the effects of the discharge itself. In addition, the influence of the ns-DBD on a shock-wave was studied. The aim was to improve the understanding of the plasma-flow interaction, a topic that is not yet fully understood, in particular for ns-DBD. The actuator was integrated in two different models, a NACA 3506 compressor blade profile and a bump geometry at the bottom of the wind tunnel. The effect of the rapid energy deposition close to the discharge was examined with the phase-locked schlieren visualisation technique. Images of the plasma acquired with short exposure times revealed information on the discharge evolution. The results show a significant effect of the flow on the discharge characteristics, in particular due to the drop of static pressure. On the other hand, no significant effect of the ns-DBD on the flow was observed due to unfavourable flow conditions, which underlines the importance of the actuator's placement.